Analysis of Differences in Employee Status on Employee Performance in the General and Civil Service Fields at the Plantation Service of North Sumatra Province - Aulia Azmi Lubis; Annio Indah Lestari Nasution (Jurnal Fokus Manajemen, 2022)
Historically, the problem of human resources is reflected in its development from the past. Even human resources, which seem to be only an internal matter of an organization, actually have a close relationship with aspects of human life and society, which have given rise to many understandings. Even human resources are as if only an internal matter of an organization. It turns out to have a close relationship with aspects of human life and society, giving rise to many interpretations. The community handles and resolves issues on a daily basis. Basically, every leader has certain powers such as appointing, regulating, transferring, recruiting, creating and also often rejecting the implementation of policies. The results of this study indicate that differences in employee status on the performance of employees serving plantations in North Sumatra have no effect. Based on the results of interview analysis conducted, there is no effect of employee performance on differences in age, seniority and training.